2023
DOI: 10.33476/jamer.v2i1.48
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lingkungan Kerja terhadap Work Engagement Melalui Motivasi Intrinsik Dosen

Abstract: Penelitian ini bertujuan mengetahui seberapa besar lingkungan kerja berdampak terhadap work engagement melalui motivasi intrinsik. Sampel penelitian berjumlah 73 orang dosen. Pengambilan sampel dilakukan di Indonesia melalui purposive sampling dengan kriteria yaitu dosen.  Data dianalisa menggunakan PLS-SEM. Hasil penelitian menemukan bahwa lingkungan kerja berpengaruh positif signifikan terhadap motivasi intrinsik dan juga work engagement. Motivasi intrinsik ditemukan memediasi pengaruh lingkungan kerja terha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The study's results found a significant positive impact of intrinsic motivation on work engagement and are supported by previous findings (Hua et al, 2020;Muchtadin, 2023;Putra et al, 2015;Shu, 2015). Nurses motivated by a job that feels good will become passionate, dedicated, and absorbed in their work.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study's results found a significant positive impact of intrinsic motivation on work engagement and are supported by previous findings (Hua et al, 2020;Muchtadin, 2023;Putra et al, 2015;Shu, 2015). Nurses motivated by a job that feels good will become passionate, dedicated, and absorbed in their work.…”
Section: Discussionsupporting
confidence: 87%
“…For workers with high intrinsic motivation, the impact given by authentic leadership will be even greater on work engagement (Shu, 2015). Intrinsic motivation positively impacts employee work engagement (Muchtadin, 2023).…”
Section: The Effect Of Intrinsic Motivation On Work Engagementmentioning
confidence: 99%